2007
DOI: 10.2337/db06-1532
|View full text |Cite
|
Sign up to set email alerts
|

GPR40 Is Necessary but Not Sufficient for Fatty Acid Stimulation of Insulin Secretion In Vivo

Abstract: Long-chain fatty acids amplify insulin secretion from the pancreatic beta cell. The G protein-coupled receptor GPR40 is specifically expressed in beta cells and is activated by fatty acids. Loss of function of GPR40 was shown to markedly inhibit fatty-acid stimulation of insulin secretion in vitro. However, the role of GPR40 in acute regulation of insulin secretion in vivo remains unclear. To this aim, we generated GPR40 knock-out (KO) mice and examined glucose homeostasis, insulin secretion in response to glu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
245
4
2

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 240 publications
(271 citation statements)
references
References 34 publications
20
245
4
2
Order By: Relevance
“…Increased insulin-releasing capacity of pancreatic islets from CLA-fed mice has been disclosed (34 -36); however, a molecular explanation for the acute insulinotropic action of CLAs is still lacking. In this study, we present several lines of evidence that acute insulinotropic effects of CLAs are mediated via activation of the ␤-cell-specific G proteincoupled receptor FFA1, an emerging therapeutic target to treat type 2 diabetes (15,16,21,27,37,38). First, increase of [Ca 2ϩ ] i and inositol phosphate production in response to CLAs was consistently observed in FFA1-expressing cells regardless of the cellular background, whereas it was not observed in cells lacking FFA1.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Increased insulin-releasing capacity of pancreatic islets from CLA-fed mice has been disclosed (34 -36); however, a molecular explanation for the acute insulinotropic action of CLAs is still lacking. In this study, we present several lines of evidence that acute insulinotropic effects of CLAs are mediated via activation of the ␤-cell-specific G proteincoupled receptor FFA1, an emerging therapeutic target to treat type 2 diabetes (15,16,21,27,37,38). First, increase of [Ca 2ϩ ] i and inositol phosphate production in response to CLAs was consistently observed in FFA1-expressing cells regardless of the cellular background, whereas it was not observed in cells lacking FFA1.…”
Section: Discussionmentioning
confidence: 92%
“…This in turn raises the possibility that FFA1 is responsible for both acute insulinotropic effects but also development of diabetes after long term ingestion of CLAs, two observations that have been made in various clinical studies with oral CLA supplementation (8, 13). So far, FFA1 has been consistently involved in mediating the acute stimulatory effects of various long chain fatty acids on insulin secretion (15,16,21,32,44,45), but it has also been implicated in potential deleterious effects of fatty acids on ␤-cell function (27,38,44), albeit the latter aspect is considered as rather controversial (27,38). Nevertheless, these aspects are of prime importance to antidiabetic drug discovery because a potential contribution of FFA1 to ␤-cell dysfunction would disqualify FFA1 agonists as novel type 2 diabetes drugs.…”
Section: Discussionmentioning
confidence: 99%
“…This is because deletion of GPR40 leads to loss of the acute insulin secretory response to fatty acids in mouse islets [128] and siRNAmediated knockdown of GPR40 in MIN6 cells also results in loss of this response [129].…”
Section: Gpr120mentioning
confidence: 99%
“…Ϫ/Ϫ Mice-GPR40 Ϫ/Ϫ mice were obtained from AMGEN Inc. As described by Latour et al (19), GPR40 Ϫ/Ϫ mice on a mixed C57BL/6/129 background were generated by homologous recombination in embryonic stem cells at Lexicon Genetics (The Woodlands, TX). Exon 2 of the GPR40 gene was replaced with a LacZ gene.…”
Section: Gpr40mentioning
confidence: 99%
“…Subsequently, the role of GPR40 (also known as free fatty acid receptor-1/FFAR-1) was mainly examined in beta cells for its involvement in insulin secretion (18). Using GPR40-deficient mice, we showed that GPR40 contributes to fatty acid potentiation of glucose-induced insulin secretion (19). Indeed, the ability of GPR40 to enhance insulin release only when glucose levels are elevated made it an appealing drug target for the treatment of type 2 diabetes, and agonists of GPR40 have shown very encouraging results in recent phase 2 clinical trials (20,21).…”
mentioning
confidence: 99%